PENGARUH KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT MELALUI KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN SEBAGAI VARIABEL MEDIASI - Jonh, Sisilia Hakiki; Putra, Iwan Setya; Klaudia, Sura (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
Abstract This research aims to analyze the influence of employee performance on community satisfaction through service quality as a mediating variable at the Sidorejo village office. This type of research is quantitative research. Data collection was carried out using a questionnaire, the data was analyzed using path analysis. The sample in this research was 100 respondents. The data analysis methods used are descriptive statistical analysis, validity test, reliability test, classical assumption test, path analysis with the help of the SPSS version 21 program. The findings of this research are 1) employee performance has a significant and direct effect on the quality of village office services Sidorejo. 2) employee performance has a significant and direct effect on the satisfaction of the Sidorejo village community. 3) service quality has a significant and direct effect on the satisfaction of the Sidorejo village community. 4) employee performance on community satisfaction does not influence (does not mediate) service quality. These findings provide input that good employee performance will create community satisfaction. Optimal service quality will create satisfaction for the community.